Pelatihan Manajemen BUMDes Berbasis Sosiokultural Masyarakat Lokal di Desa Sukamaju - Nursetiawan, Irfan; Yuliani, Dini; Prabowo, Faizal Haris Eko; Sobari, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Improving the welfare of rural communities in rural areas is an urgency in every community empowerment activity. One of the institutions that can improve the welfare of village communities, namely Village Owned Enterprises (in Indonesian is BUMDes). However, BUMDes have not contributed significantly and are optimally managed. This activity aims to apply the pattern of understanding the management of BUMDes Maju Mandiri in Sukamaju Village, Cihaurbeuti District, Ciamis Regency. In addition, this activity can make a positive contribution to the economic empowerment of rural communities through a pattern of BUMDes activities based on socio-cultural rural communities to increase the income and welfare of rural communities. The principle of gotong royong and participation is the main vocalist in Community Based Empowerment (in Indonesian is PKM) activities. This activity is carried out through mentoring methods which include: (1) the program initiation stage; (2) implementation stage; and (3) monitoring and evaluation stages. This activity resulted in an increase in the knowledge and skills of BUMDes managers by 50% in the management organization, so that the institution is managed quite well. In addition, there is an increase in the understanding of BUMDes managers by 75% in business management and has an impact on increasing innovation, as well as sales of BUMDes superior products.